The Effect of Organizational Justice Components on Occupational Combustion among Workers in Primary Health Care Centers in Jeddah Governorate - Mahdi, Khadija Ali; Al Shamasi, Areej Abdul Rahman (Journal of Economic, Administrative and Legal Sciences, 2017)
The objective of the current study was investigating the influences of organizational justice dimensions on occupational burnout among workers in primary healthcare centers in Jeddah Governors. In addition, the current study intended to examine the relationships between the demographic factors and worker’s perceptions in primary healthcare centers of organizational justice practices and the relationships between the demographic factors and their feelings of organizational justice and occupational burnout in their workplaces. Moreover, the study aimed at investigating the level of occupational burnout among primary healthcare centers workers.   The researcher used the descriptive analytical methodology that depends on the phenomenon study as if it is actually noticed, and pays attention to its accurate description, and highly expressed it in terms of quality and quantity. The current study is applied on a sample of the employees working at the five sectors of the primary healthcare in Jeddah, with sample size reaching (100) after choosing one center from each sector. A questionnaire was used to measure the study variables in addition to using SPSS for data analysis. The main results of the study are stated as: the justice procedures, distribution and treatment have an impact on occupational burnout, through an inverse relationship appearing among the study aspects, this means that the increasing independent variables decline occupational burnout. The study suggests many recommendations: The importance of highlighting the vision, mission, policies and objective clearly and reveal those centres' role as a part of the health care. Nevertheless, it is essential to qualify the primary health care directors in order to be highly experienced in this type of administration, and taking decisions related to employees and their tasks in accordance with sufficient and clear information. Finally, it is essential to assess the employees’ satisfaction about the procedures, treatment and distributions periodically and same as the yearly assessment.
Keywords: Burnout; Primary Healthcare centers; Workers in Primary Healthcare; Organizational Justice Dimensions